Plus ça change? The COVID-19 pandemic as continuity and change as reflected through risk theory. (17th November 2021) - Alaszewski, Andy
Abstract : On 30 December 2019, Dr Marjorie Pollack, deputy editor of ProMed, received information about a SARS-like disease in the Chinese city of Wuhan. Having checked the facts, she issued an alert to the worldwide network signalling the start of an outbreak of a highly infectious and dangerous disease. The new virus, SARS-CoV-2 spread rapidly from Wuhan causing a global pandemic of COVID-19. In this review, I examine the ways in which risk can provide insights into and an understanding of the social and cultural responses to the COVID-19 pandemic. I draw on three major theories that highlight the role of risk in contemporary societies: Beck and Giddens's analysis of late modern society as risk society; Douglas's analysis of the continuing significance of cultural theory in understanding the construction and use of risk to address social tensions and challenges; and Foucault's analysis of governmentality and the use of discourses such as risk as a form of power and control.